At the Heart of Learning (Series: Paper 4 of 4): Kuranyu-kutu nyakula nyaan nyanganyi? Imagining the Future. Issue 1 (March 2014) - Burton, Rueben; Osborne, Sam
Mainstream Australian society tends to assume that the purposes of schooling and aspirations that school should enable are universal and roundly accepted. The authors of this paper examine the issues with these assumptions and consider what "imagined futures" (Nakata, 2007a) mean for young people in An angu (Pitjantjatjara/Yankunytjatjara) schools and communities today. They pose the question, "How might remote educators enable a space for re-imagining the future on An angu terms and what potential does remote education offer in this regard?" This paper emphasizes the strong self-determination stance and action that is required by An angu in both articulating An angu values in the education process and in instilling a positive perspective about the opportunities for young people into the future. The authors also interrogate the role of Pir anpa (non-Indigenous) remote educators in how they might position themselves for student imagination, aspiration and hope, pointing students back to the intergenerational capacities that are critical in this regard.